Successful manual thrombus aspiration in anterior ST-segment elevation myocardial infarction due to cardioembolic obstruction of the left main coronary artery. Issue 2 (February 2020) - Della Riva, Diego; Bruno, Matteo; Taglieri, Nevio
Abstract: Large clinical trials and meta-analyses have shown that thrombus aspiration (TA) in the setting of ST-T segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) does not improve clinical outcome, whilst it may be associated with an increased risk of stroke. Accordingly, in the most recent European Society of Cardiology guidelines the role of routine TA during PPCI has been downgraded to a class III recommendation with level A of evidence. On the other hand, it has been suggested that in case of high thrombus burden a selective use of TA may still play a role. STEMI due to cardioembolism (CE) definitely represents one of these situations. In the present case of an 81-year-old woman presenting with STEMI due to a cardioembolic obstruction of left main coronary artery, we show that TA succeeded, whereas classical angioplasty failed, in promoting a prompt coronary flow restoration in a life-threatening condition. Further, it allowed us not to upgrade the procedure with stent implantation that would have required a triple antithrombotic therapy, significantly increasing the bleeding risk. Visual examination of thrombi retrieved suggested the diagnosis of CE. Finally, we clearly show which is the mechanism linking TA with the risk of stroke. <Learning objective: Recent European Society of Cardiology guidelines have downgraded thrombus aspiration (TA) in the setting of ST-T segment elevation myocardial infarction (STEMI) to a class III recommendation with level A of evidence. Nevertheless, we show a case where TA can still be useful as bail out therapy to treat a critical condition, to diagnose a rare mechanism of STEMI, and to understand the mechanism linking its use to the increased risk of stroke.>